2020
DOI: 10.4103/aian.aian_45_19
|View full text |Cite
|
Sign up to set email alerts
|

Association of APOE gene polymorphism with stroke patients from rural Eastern India

Abstract: Context: Studies from the different ethnic regions of the world have reported variable results on association of APOE gene polymorphism in stroke. Aim: The aim of this study is to find out the possible association of APOE polymorphism in stroke patients in ethnic Bengali population. Settings and Design: A prospective case–control study was undertaken in the Department of Neurology, Burdwan Medical College, Burdwan, West Bengal, India, over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…4 Moreover, it is reported that genetic factors play a role in the pathophysiological process of IS. Several studies had revealed a hereditary predisposition to IS susceptibility, such as polymorphisms in apolipoprotein E (APOE), ATP-binding cassette transporter 1 (ABCB1), and interferon-beta 1 (IFNB1), [5][6][7] but there are still many riskrelated genetic polymorphisms that have not been discovered. Wnt are a group of glycoproteins that play a key role in the proliferation, differentiation, and migration of adult neural stem/progenitor cells (NS/PC) in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Moreover, it is reported that genetic factors play a role in the pathophysiological process of IS. Several studies had revealed a hereditary predisposition to IS susceptibility, such as polymorphisms in apolipoprotein E (APOE), ATP-binding cassette transporter 1 (ABCB1), and interferon-beta 1 (IFNB1), [5][6][7] but there are still many riskrelated genetic polymorphisms that have not been discovered. Wnt are a group of glycoproteins that play a key role in the proliferation, differentiation, and migration of adult neural stem/progenitor cells (NS/PC) in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, it is reported that genetic factors play a role in the pathophysiological process of IS. Several studies had revealed a hereditary predisposition to IS susceptibility, such as polymorphisms in apolipoprotein E ( APOE ), ATP-binding cassette transporter 1 ( ABCB1 ), and interferon-beta 1 ( IFNB1 ), 5–7 but there are still many risk-related genetic polymorphisms that have not been discovered.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that carriers of the ɛ 4 allele show an increased risk of ICH but ɛ 2 allele carriers are not at risk of having ICH in the future. Recent research indicated that the occurrence of the APOE ɛ 4 allele significantly increases the risk of IS in the populations from rural Eastern India [ 67 ], China [ 68 ], and Korea [ 69 ], and deteriorates cognitive function [ 70 ]. However, the influence of ApoE4 in pre-and post-stroke is not clear.…”
Section: Apolipoprotein E In Ad and Strokementioning
confidence: 99%